Life Instinct Experience Reflected In Jenny Downham's Novel Before I Die (2007): A Psychoanalytic Perspective - Suryaningrum, Radityawati; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This research paper is aimed to show a visible image of Jenny Downham's novel which is analyzed by using psychological perspective. The objectives of the research are to analyze the novel based on the structural elements and to analyze on the psychoanalytic perspective proposed by Sigmund Freud. This research paper belongs to qualitative research. Data of the research is divided into primary data and secondary data. The primary data of the research is "Before I Die" novel and secondary data of the research are website, dictionary, and some books that support the analysis. The method to analyze this data is descriptive analysis. Based on the psycholoanalytic perspective analysis, Jenny Downham illustrated psychological phenomena in which an individual has experienced internal and external conflict. The outcome of the study shows that Jenny Downham illustrates the psychological phenomenon when an individual submits herself fully to her own instinct.